Unlocking opportunities for youth through food systems transformation - Kirui, L.; Ronoh, N. (2025)
The blog underscores that young people are crucial for transforming food systems, but they face significant barriers: lack of access to land, financing, training aligned with labor market demands, and sustainable productive opportunities. The article reports on deliberations from the 8th KIPPRA Regional Conference in Kenya, highlighting evidence that strengthening skills (including soft skills), relevant technical education, multi-stakeholder partnerships, and meaningful youth participation can unlock profitable and sustainable economic opportunities in agriculture and related sectors. The approach emphasizes that a just and inclusive transition requires designing policies and programs that recognize and remove structural barriers for young people, including gender-based barriers.